Analysing the understanding of the implementation of curriculum 2005 by grade four educators in Mangaung - Dyantyi, Vuyo Cedric (University of the Free State, 2003)
This study focussed on analysing the understanding of curriculum 2005 and its implementation by Grade 4 educators in Mangaung. Six respondents from three different schools in the Mangaung area, were selected with the express purpose of investigating their understanding of curriculum 2005 and its implementation. The Free Attitude Interview was used as the technique to gather information from the respondents. The purpose was to find out what understanding do these educators bring to curriculum 2005 and its implementation. To arrive at the findings mentioned below, this research used the Textually Orientated Discourse Analysis (TODA) as a technique for analysing data, from the six respondents of 3 different schools which were selected. A tape recorder was used to capture all conversations verbatim. This meant that the transcripts of the interviews were made, translated and later interpreted. The (TODA) technique was found useful in interpreting the respondents discourses. The text word of the respondents were analysed and interrogated in order to disclose the influence of the ideology carried by the respondent. The results elicited through TODA as a technique, indicated that educators face pressures and demands in their everyday lives. This is as a result of struggling to understand the contents of curriculum 2005 and its implementation in order to successfully implement curriculum 2005. Based on the findings, the study recommends that the inservice teacher upgrading programmes need to be organised towards implementation of curriculum 2005 and other factors that might impact on educators' understanding of curriculum 2005 and its implementation.
Dissertation (M.Ed. (Education))--University of the Free State, 2003
Keywords: Curriculum 2005; Educators; Grade 4 educators; Curriculum 2005 implementation